Coexistence of seven different carbapenemase producers in a single hospital admission screening confirmed by whole-genome sequencing - Frieder Fuchs; Kyriaki Xanthopoulou; Tessa Burgwinkel; Rocío Arazo del Pino; Esther Wohlfarth; Florian Pavlu; Ralf M. Hagen; Paul G. Higgins (Journal of Global Antimicrobial Resistance)
Objective: To molecularly characterize several extensively drug-resistant isolates from a single hospital admission screening of a war-injured patient from Ukraine. Methods: Admission screening included swabs from skin, wounds, catheters, nasopharyngeum and rectum. Bacterial identification, antimicrobial susceptibility testing and rapid multiplex PCR assays targeting resistance genes were performed during routine diagnostics. Isolates positive by PCR had their genomes sequenced using short- and long read-platforms (MiSeq and MinION) to confirm species, identify resistance genes and plasmids and investigate clonality with core-genome MLST. Results: Seven Gram-negative pathogens (Acinetobacter baumannii (n = 2; ST78, ST2), Klebsiella pneumoniae (n = 2; ST395), Pseudomonas aeruginosa (n = 1; ST1047), Escherichia coli (n = 1; ST46), Enterobacter cloacae complex (n = 1; ST231)) were molecularly confirmed non-identical. Antimicrobial susceptibility testing showed resistance to carbapenems (7/7 isolates) and last-resort treatment options such as ceftazidime-avibactam (6/7 isolates) and cefiderocol (4/7 isolates). All isolates were colistin susceptible. Sequencing identified the E. cloacae complex as Enterobacter hormaechei subsp. xiangfangensis. Six acquired carbapenemase genes (blaIMP-1, blaNDM-1, blaOXA-48, blaNDM-5, blaOXA-23 and blaOXA-72) were detected. Both A. baumannii isolates differed in sequence type, carbapenemases and cefiderocol susceptibility. Both K. pneumoniae isolates shared sequence type and some resistance genes on an IncR plasmid but were different in core-genome MLST and carbapenemases (OXA-48 or NDM-1). One vancomycin-resistant Enterococcus faecium was also detected (VanA). Conclusions: War-injured patients from Ukraine may carry different clones of multidrug-resistant pathogens with limited treatment options and diverse resistance genes at risk for dissemination. Infection control measures should include early molecular characterization of isolates for detection of routes of transmission.